Dissociating neural signatures of mental state retrodiction and classification based on facial expressions - Kang, Kathleen; Schneider, Dana; Schweinberger, Stefan R.; Mitchell, Peter (Oxford University Press, 2018)
Posed facial expressions of actors have often been used as stimuli to induce mental state inferences, in order to investigate “Theory of Mind” processes. However, such stimuli make it difficult to determine whether perceivers are using a basic or more elaborated mentalizing strategy. The current study used as stimuli covert recordings of target individuals who viewed various emotional expressions, which caused them to spontaneously mimic these expressions. Perceivers subsequently judged these subtle emotional expressions of the targets: In one condition (“classification”) participants were instructed to classify the target’s expression (i.e., match it to a sample) and in another condition (“retrodicting”) participants were instructed to retrodict (i.e., infer which emotional expression the target was viewing). When instructed to classify, participants showed more prevalent activations in event-related brain potentials (ERPs) at earlier and mid-latency ERP components N170, P200 and P300-600. By contrast, when instructed to retrodict participants showed enhanced late frontal and rontotemporal ERPs (N800-1000), with more sustained activity over the right than the left hemisphere. These findings reveal different cortical processes involved when retrodicting about a facial expression compared to merely classifying it, despite comparable performance on the behavioural task